CONSUMER PURCHASING BEHAVIOR OF HALAL COSMETICS: A STUDY ON GENERATIONS X AND Y - Elfira Maya Adiba (Journal of Islamic Monetary Economics and Finance, 2019)
The halal economic industry is currently developing not only in Indonesia, but also on the global level. The global economic sector is not only limited to the sharia financial sector and halal food, but also halal cosmetics. The increasing number of Muslim population in the world has caused the increasing demand for halal cosmetics, as many other factors influencing the demand for halal cosmetics. The purpose of this study is to examine the influence of halal knowledge and Islamic religiosity toward customer behavior that is mediated by consumer attitude. Data were collected from questionnaires distributed to respondents in Surabaya, Sidoarjo, and Gresik, East Java, Indonesia. 145 respondents were identified as generation Y, while 40 as generation X. Primary data were analyzed by PLS. The results showed that halal knowledge and Islamic religiosity had a significant effect on consumer behavior perfectly mediated by attitude. Such results give implication to the halal cosmetics company to design appropriate marketing strategies in order to increase Indonesian exports for halal products, so it could help the national economy.